“是” [shì] НИНГ ГРАММАТИК САТҲ ЭЛЕМЕНТИ СИФАТИДА ҚЎЛЛАНИЛИШИГА ОИД АЙРИМ МУЛОҲАЗАЛАР - Тўхтамишев, А. (SCIENCE and SOCIETY, 2023)
This article is devoted to the analysis of the use of the verb "是" [shì] in the Chinese language. In ancient Chinese, "是" [shì] was widely used, that is, it performed various functions in speech. However, the scope of use in modern Chinese is limited. Given the variety of its functions, in this article we will look at "是" [shì] as part of speech and syntactic.